Le « rapport Stora » : un premier débat sur les enjeux mémoriels - Didier Monciaud (Cahiers d’histoire.)
At Emmanuel Macron’s request, Benjamin Stora launched a report, dedicated to the Algerian war and the memorial questions of the colonisation. This is a sensitive a complex subject, not only for the relationship between the two countries, but also for the french society. Lately, the context was marked by a wave of nostalgia for the colonial period. This 146 page document, delivered on the 20th of January 2021, was aimed at opening a dialogue between the different memories, through propositions to build the reconciliation. It raised a major debate, both in Algeria and in France. We selected here, a full spectrum of opinions, published shortly after its release in early 2021, which go from support to rejection, and other critical positions.